Accounting System Design Using Microsoft Access At Pt. Nasional Global Karimun - Ivone Ivone; Natasya Des T.G (Universitas Internasional Batam, 2023)
Indonesia has many advanced companies which are the center of interest for foreign investors. These companies generally have a system to process the company's internal data, so it's easier for the company to eliminate fraud and error. Unfortunately, many companies in Indonesia, especially small-scale companies, still need to implement a accounting system using technology that is currently available for free. PT. Nasional Global Karimun is one of those companies that still use Microsoft Excel and records activities through company books. Through this community program, a more optimal and efficient accounting system was designed for PT. Nasional Global Karimun using the Microsoft Access. In collecting related data needed in system design, interviews were carried out with employees and direct observations at partner locations. The condition of the company before and after the implementation of the Microsoft Access-based accounting system is also documented. There are several differences that are perceived after implementing an accounting system using Microsoft Access. Employees find it easier to find unpaid receivables and errors in recording transactions. Financial reports that are formed automatically make it easier for employees because they are more efficient and effective. Although the implementation went smoothly, there is recommendation that can be given for further research, namely adding an online-based system to the accounting system.